Starch-based food inks in extrusion 3D printing: formulation, physico-chemical properties and printing performance - Kabus, Conrad John (Kansas State University, 2024)
Food 3D printing offers the possibility of manufacturing novel products with intricate shapes, unique textures, and alternative methods for delivering nutrition. This research aims to understand the impact of key formulation attributes for 3D printing inks, such as starch source and plasticizers (sucrose and moisture), on their physico-chemical properties and rheology, printing performance, and end-product texture. Impact of 3D printing process parameters on end-product quality was also assessed. The focus of this thesis was to study the rheological and physico-chemical properties of starch-based food inks and how they impact performance for extrusion based printing, but the knowledge gained in this research can be transferred to other types of printing technology as well, including other types of protein and chocolate-based food 3D printing. In the first part of the study, 3D printing inks were formulated based on a degermed corn flour or wheat base with varying level of sucrose (0, 4, 8 and 12%) while keeping the moisture constant at 50% wb in a 2x4 factorial design; and varying levels of water (50, 54, 58 and 62% wb) with no sucrose in the formulation in another 2x4 factorial design. Sucrose inclusion up till 12% significantly decreased the rapid visco analyzer (RVA) pasting viscosity of both corn-based (from 4655 to 1410 mPa.s) and wheat-based formulations (from 2591 to 703 mPa.s). Peak gelatinization temperature obtained using differential scanning calorimeter, increased from 73.6 to 77.2°C and from 65.5 to 69.0°C for corn and wheat-based inks, respectively, as sucrose level increased in the abovementioned range. Phase transition analyzer (PTA) data had conflicting results as sucrose level increased, with flow temperature decreasing from 130 to 91°C for corn- based inks, showing a clear plasticizing effect; but increasing from 101 to 147°C for wheat- based inks, which indicated competition for water between sucrose and starch might have had an important role, which was also affirmed from water absorption index data. Products based on corn-based inks had considerably poor 3D printing performance with increase in moisture content from 50-62% as ascertained by the dimensional distortion ratio (DDR) as compared to wheat-based inks (DDR absolute values of 0.032 to 1.110 for corn as compared 0.040 to 0.092 for wheat). Both corn and wheat-based 3D printed samples showed more resiliency in shape and dimensional distortion with increase in sucrose content, although wheat products exhibited an increase in DDR as sucrose level increased. 3D printed product was also tested using RVA and DSC, with results indicating that corn-based prints were only partial gelatinized, while wheat- based prints were completely gelatinized during the process. In the second part of this study, rheology of corn and wheat-based food inks were evaluated using a dynamic rheometer. In general, frequency sweep storage modulus (G’) and loss modulus (G”) values decreased (p < 0.05) for both corn and wheat-based inks with increase in sucrose inclusion levels from 0-12%, showing a plasticizing effect that was partly contradictory to the results obtained from PTA earlier. The order of magnitude of G’ and G” for corn (~10⁴-10⁵ and ~10³-10⁴ Pa, respectively) were higher than that for wheat-based inks (~10³-10⁴ and ~10³ Pa, respectively). Impact of 3D printing infill density (20, 40, 60 and 80%) was also investigated. DDR for corn-based ink increased significantly from 0.064 to 0.701, as 3D printing infill density was varied from 20-80%; while the DDR for wheat-based ink was more resilient with no significant differences with change in infill density (DDR ranging from -0.026 to -0.052). High infill density significantly increased the structural integrity both corn and wheat-based 3D printed products. At infill density of 20%, an average peak force of 4.59 and 3.75 kg was observed for corn and wheat-based 3D printed products, respectively, as determined by a texture analyzer in compression mode; while at 80% infill density corn and wheat-based products had average peak force of 21.16 and 24.70 kg, respectively. In conclusion, key methodology was developed for evaluating physico-chemical properties and performance of food inks. The approach outlined in this study can help to design high performance materials for food 3D printing in the future.
Keywords: Food 3D printing; Extrusion; Starch; Rheology; Printability